2015
DOI: 10.1002/j.0022-0337.2015.79.3.tb05889.x
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Academic Performance of Dental Students Using Perception of Educational Environment

Abstract: Greater emphasis on student-centered education means that students' perception of their educational environment is important. The ultimate proof of this importance is its effect on academic performance. The aim of this study was to assess the predictability of dental students' grades as indicator of academic performance through their perceptions of the educational environment. The Dundee Ready Educational Environment Measure (DREEM) questionnaire was used to assess dental students' perceptions of their educati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
45
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(54 citation statements)
references
References 21 publications
6
45
2
1
Order By: Relevance
“…In the present study, no significant statistical difference was observed between students with the Excellent (A) score and those with the average rating (C) regarding the DREEM score in similarity to (Al-Ansari et al 2015) who reported no association between GPA and the DREEM score at baseline. One explanation of the result is that the perception of the environment may ultimately differ at the time of the survey and the time of the examination whose GPA was reported by the students.…”
Section: Discussioncontrasting
confidence: 83%
“…In the present study, no significant statistical difference was observed between students with the Excellent (A) score and those with the average rating (C) regarding the DREEM score in similarity to (Al-Ansari et al 2015) who reported no association between GPA and the DREEM score at baseline. One explanation of the result is that the perception of the environment may ultimately differ at the time of the survey and the time of the examination whose GPA was reported by the students.…”
Section: Discussioncontrasting
confidence: 83%
“…Results allowed a thorough interpretation of strengths and weaknesses related to learning environment; however, more negative than positive changes were reported between what was expected and what they actually experienced (KANG et al, 2015). Other longitudinal study showed that students of the second year had a better perception of the teaching environment than students of the sixth year for D1 (students' perception of learning), D2 (students' perception of teaching) and D5 (students' social self-perception) (AL-ANSARI; EL TANTAWI, 2015). Similarly, in the study by Kang et al (2015), total DREEM score between second, third and Rev.…”
Section: Discussionmentioning
confidence: 82%
“…Several studies (AHMAD et al, 2015;AL-ANSARI, EL TANTAWI, 2015;CHANDRAN;RANJAN, 2015;STURM;SARTORATO, 2005;FARAJPOUR et al, 2017;KANG et al, 2015;MYINT et al, 2016) applied DREEM questionnaire to evaluate teaching environment in different universities, mostly Dentistry or Medicine undergraduate courses. This evaluation allowed the generation of a profile and highlighted the strengths and weaknesses regarding the educational environment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations